Examining the Types of Pronoun in Ancient ages - Maroofi, Safiullh; sateh, Sayed Jan; Rashidi, Abdul Matin Rashidi (Journal of diversity in learning (JDIL), 2024)
The pronoun is one of the independent words and is considered as a group of nouns and replaces nouns, prevents the repetition of nouns in words. Of course, the name that has already been mentioned in the word; Pronouns are divided into: personal or subject pronouns, sign pronouns, common pronouns, possessive pronouns, interrogative pronouns, important pronouns and pronouns. Personal pronouns in the ancient language did not have sex (male and female) and have three forms: singular, duplicate and plural. The pronoun is also used singular, duplicate and plural. The interrogative pronouns are who, what and which are and somehow come at the beginning of the sentence. Ambiguous pronouns are interrogative pronouns and have singular, masculine and Mont verb forms. The pronouns have different forms ta - ha, ha and fa, which are used for masculine, feminine and even. Possessive pronouns are used in different forms such as triple and triple gender, and common pronouns can also be utilized.